(untitled) (Estudio Agustiniano, 2018)
The study of this pictographic catechism covers some particularities that are not found in other pictographic catechisms. Of course all of them are unique because of their status as manuscripts; but in the present case its content, as well as its structure have some unexpected original details. To approach the study of this one therefore requires a more precise description.